Time-dependent behaviour of cracked, partially bonded reinforced concrete beams under repeated and sustained loads. (15th May 2018) - Daud, Sultan A.; Forth, John P.; Nikitas, Nikolaos
Highlights: Shrinkage cannot be applied as uniform in cracked beams in Midas FEA. Bonded and unbonded beams have similar long-term behaviour under repeated loads. Long-term, concrete develops higher strains in the compression than in the tension zone. Midas-FEA can replicate long-term concrete testing after modelling modifications. Abstract: This paper compares the flexural behaviour of cracked partially bonded (in the mid-span, maximum moment zone) reinforced concrete beams subjected to (i) static sustained load and (ii) static sustained with cyclically repeating load. Information relating to surface strains and mid-span deflections were continuously recorded for a period of 90 days. The sustained load level represented that which produced the stabilized crack pattern. The amplitude of the superimposed cyclic load was considered to be a small fraction of the sustained load. The experimental outcome shows that under sustained load alone, the long-term mid-span deflection of reinforced concrete beams with artificially debonded reinforcement is substantially higher than that of normally bonded equivalent beams. For the cyclically exerted load addition there was no substantial difference between the observed ultimate deformations of bonded and debonded beams. Nonlinear finite element software (Midas FEA) was used to simulate these results and it was found that a numerical-experimental match can be achieved after applying necessary modifications to the distribution of shrinkage down through the beams' cross-section.